Tracing a Narrative of Muslim Self-Aftermath of 9/11 in Monica Ali’s Brick Lane: Islamophobia in the West - Ahmed Saad Aziz (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2018)
This study is aimed at finding a narrative of Muslim self-aftermath of 9/11 in the West when it was swept with hatred against Muslims leading to the rise of Islamophobia which is herself experienced by the novelist, Monica Ali. Penning from her own experience, the novel, Brick Lane (2003) can be considered as real experience of many people who were held responsible for crime committed. This study employs descriptive qualitative method in dealing with the rise of islamophobia in the West after the incident of 9/11. This is the textual analysis of the experiences of diasporic Muslim couple from Bangladesh living in London and being the witness of the rise of xenophobia in the form of islamophobia aftermath of 9/11. This evaluation and interpretation are importance in the contemporary scenario as there is a continuous rise of such incidents in Europe and America in different ways. The outcome of these incidents is that it is mostly the innocent Muslims who are being attacked for a crime committed by others.The result shows the bitter experience of simple Bangladeshi Muslims immigrant who struggled for identity crisis in a multicultural highly educated world. It also reflects the personal experiences of writer herself as she being a Bangladeshi is living in West. The result was evaluated by examining Bangladeshi immigrant characters and their various circumstances and situations in the novel. Moreover, the point is that people of South Asian countries like India, Pakistan, Bangladesh, Nepal, Sri Lanka and Afghanistan prefer to live and work in West for better standard of living, education and job prospects.